Hydrolysis at One of the Two Nucleotide-binding Sites Drives the Dissociation of ATP-binding Cassette Nucleotide-binding Domain Dimers - Zoghbi, Maria E. (American Society for Biochemistry and Molecular Biology, 2013)
The functional unit of ATP-binding cassette (ABC) transporters consists of two transmembrane domains and two nucleotide-binding domains (NBDs). ATP binding elicits association of the two NBDs, forming a dimer in a head-to-tail arrangement, with two nucleotides “sandwiched” at the dimer interface. Each of the two nucleotide-binding sites is formed by residues from the two NBDs. We recently found that the prototypical NBD MJ0796 from Methanocaldococcus jannaschii dimerizes in response to ATP binding and dissociates completely following ATP hydrolysis. However, it is still unknown whether dissociation of NBD dimers follows ATP hydrolysis at one or both nucleotide-binding sites. Here, we used luminescence resonance energy transfer to study heterodimers formed by one active (donor-labeled) and one catalytically defective (acceptor-labeled) NBD. Rapid mixing experiments in a stop-flow chamber showed that NBD heterodimers with one functional and one inactive site dissociated at a rate indistinguishable from that of dimers with two hydrolysis-competent sites. Comparison of the rates of NBD dimer dissociation and ATP hydrolysis indicated that dissociation followed hydrolysis of one ATP. We conclude that ATP hydrolysis at one nucleotide-binding site drives NBD dimer dissociation.